Preparation method of spherical mesoporous carbon material, spherical mesoporous carbon material and method for detecting components in cigarette paper

Through the analysis of spherical mesoporous carbon materials as adsorbents combined with gas chromatography-mass spectrometer, the problems of low concentration and complex samples in smoke paper detection are solved, the detection sensitivity is improved, the sample pretreatment process is simplified, and the di-isopropylene is achieved Rapid and accurate detection of polynaphthalene, polychlorinated biphenyls and photoinitiators.

CN119284871APending Publication Date: 2025-01-10JILIN TOBACCO IND CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411372148.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the detection of smoke paper, there are problems such as low concentration, complex sample components, many interfering substances, and susceptible to environmental factors, resulting in complex sample pre-processing and insufficient detection sensitivity.

Method used

Spherical mesoporous carbon material is used as the dispersed solid-phase extraction adsorbent. The preparation method includes adding sodium polyacrylate and silica sol to the sucrose solution, followed by concentrated sulfuric acid, heating reaction and calcining, eliminating the silicon template, and obtaining highly dispersible spherical mesoporous Carbon material, combined with gas chromatography-mass spectrometer analysis to detect diisopropylnaphthalene, polychlorinated biphenyl and photoinitiators.

Benefits of technology

It improves adsorption performance and detection sensitivity, simplifies the sample pretreatment process, reduces the matrix effect, and achieves rapid and accurate detection of various substances in smoke paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284871A_ABST
    Figure CN119284871A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a spherical mesoporous carbon material. The method comprises the following steps: obtaining a sucrose solution; adding sodium polyacrylate into the sucrose solution; adding silica sol into the sucrose solution added with sodium polyacrylate, and uniformly mixing; adding concentrated sulfuric acid into the sucrose solution added with sodium polyacrylate and silica sol, uniformly mixing, and heating for reaction; washing the reaction product to be neutral, and then drying the reaction product; grinding the dried reaction product, and calcining in a nitrogen atmosphere; and eliminating the silicon template in the reaction product to obtain the spherical mesoporous carbon material. The invention also provides a spherical mesoporous carbon material and a method for simultaneously detecting diisopropylnaphthalene, polychlorinated biphenyl and a photoinitiator in paper for cigarettes. According to the preparation method of the spherical mesoporous carbon material, the prepared high-dispersity spherical mesoporous carbon material is developed in pore structure and high in specific surface area, more adsorption sites can be provided, and the mesoporous structure is beneficial to rapid diffusion of the material in a solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sample pretreatment, and in particular to a method for preparing a spherical mesoporous carbon material, a spherical mesoporous carbon material, and a method for detecting components in cigarette paper. Background Art

[0002] Sample pretreatment technology has become the bottleneck of the entire analysis process. Cigarette paper analysis has the characteristics of low concentration of the measured substance, complex sample components, many interfering substances, coexistence of multiple isomers, and susceptibility to environmental factors, which usually requires a complex sample pretreatment process. Cigarette paper detection technology focuses on the detection of one or a class of substances. For the simultaneous analysis of multiple substances, high-resolution detection instruments with high sensitivity and good selectivity are required. In the commonly used dispersed solid phase extraction technology, the adsorbent is the core, and its performance has an important influence on the accuracy and sensitivity of the analysis. Therefore, it is particularly important to develop new adsorption materials for sample pretreatment. Summary of the invention

[0003] To at least partially solve the above problems, according to the first aspect of the present application, an embodiment of the present application provides a method for preparing a spherical mesoporous carbon material, the method comprising: obtaining a sucrose solution; adding sodium polyacrylate to the sucrose solution; adding silica sol to the sucrose solution with sodium polyacrylate added, and mixing evenly; adding concentrated sulfuric acid to the sucrose solution with sodium polyacrylate and silica sol added, mixing evenly, and heating to react; washing the reaction product to neutrality, and then drying the reaction product; grinding the dried reaction product, and then calcining it in a nitrogen atmosphere; eliminating the silicon template in the reaction product to obtain a spherical mesoporous carbon material.

[0004] In some embodiments, the mass ratio of sucrose to sodium polyacrylate in the sucrose solution is 1:(0.0013-0.0022).

[0005] In some embodiments, the mass ratio of sucrose to sodium polyacrylate in the sucrose solution is 1:(0.0017-0.0018).

[0006] In some embodiments, the relationship between the mass of sucrose in the sucrose solution and the volume of the silica sol is 1 g: (0.56-0.66) mL; the relationship between the mass of sucrose in the sucrose solution and the volume of concentrated sulfuric acid is 1 g: (0.24-0.34) mL; the concentration of sucrose in the sucrose solution is (0.21-0.24) g / mL.

[0007] In some embodiments, after adding silica sol to a sucrose solution to which sodium polyacrylate is added, stirring is performed at room temperature for 55 to 65 minutes to mix evenly; after adding concentrated sulfuric acid to a sucrose solution to which sodium polyacrylate and silica sol are added, stirring is performed for 55 to 65 minutes to mix evenly, and the stirred solution is placed in an oven at 95°C to 105°C for aging for 23 to 25 hours to increase the temperature for reaction; after washing the reaction product to neutrality, drying it in an oven at 75°C to 85°C to dry the reaction product; grinding the dried reaction product, calcining it at 850°C to 950°C in a nitrogen atmosphere for 2.5 to 3.5 hours; using a NaOH solution or a HF solution to eliminate the silicon template in the reaction product.

[0008] According to the second aspect of the present application, an embodiment of the present application provides a spherical mesoporous carbon material, wherein the specific surface area of ​​the spherical mesoporous carbon material is 705 to 771 m 2 / g.

[0009] In some embodiments, the pore volume of the spherical mesoporous carbon material is 0.36-0.37 cm 3 / g.

[0010] According to the third aspect of the present application, an embodiment of the present application provides a method for simultaneously detecting diisopropylnaphthalene, polychlorinated biphenyls and photoinitiators in cigarette paper, the method comprising: cutting cigarette paper into pieces; putting the cut cigarette paper into a dichloromethane extraction solvent, and then adding three mixed internal standard solutions of deuterated pyrene, deuterated phenanthrene and deuterated acenaphthene, and ultrasonic extraction; extracting the extract, adding the spherical mesoporous carbon material prepared by the preparation method of spherical mesoporous carbon material provided by any embodiment of the present application to the extract, vortexing, and centrifuging after oscillation; taking the supernatant after centrifugation and analyzing it with a gas chromatography-mass spectrometer to detect diisopropylnaphthalene, polychlorinated biphenyls and photoinitiators in the cigarette paper.

[0011] In some embodiments, the mass ratio of the cigarette paper to the mass ratio of the spherical mesoporous carbon material is 1:(0.035-0.045); the vortex oscillation time is 25 min-35 min, and the oscillation rate is 550 rpm-650 rpm.

[0012] In some embodiments, the chromatographic conditions are: helium as carrier gas, the injection port temperature is 300°C, the injection volume is 1 μL, and the injection mode is splitless injection; the column oven temperature program is: 60°C, maintained for 2 minutes, heated to 170°C at a rate of 40°C / min, then heated to 180°C at a rate of 2°C / min, maintained for 10 minutes, and finally heated to 300°C at a rate of 25°C / min, maintained for 20 minutes; the mass spectrometry conditions are: the transmission line temperature is 300°C, the ion source temperature is 280°C; the quadrupole temperature is 150°C, the solvent delay is 6 minutes, and the selected ion mode is adopted.

[0013] The preparation method of spherical mesoporous carbon material provided in the embodiment of the present application uses silica sol as a template, selects sucrose as a carbon source, concentrated sulfuric acid as a catalyst, and sodium polyacrylate as a dispersant. The material is simple and environmentally friendly, the cost is low, and the synthesis rate is fast. The prepared highly dispersible spherical mesoporous carbon material has a developed pore structure and a high specific surface area, which can provide more adsorption sites, and the mesoporous structure is conducive to the rapid diffusion of the material in the solution, which can improve the adsorption performance of the material and enhance the adsorption amount of the material on non-target substances. The method for simultaneously detecting diisopropylnaphthalene, polychlorinated biphenyls and photoinitiators in cigarette paper provided in the embodiment of the present application uses highly dispersible spherical mesoporous carbon materials as dispersed solid phase extraction adsorbents, combined with gas chromatography-mass spectrometry analysis, to establish a detection method for simultaneously analyzing diisopropylnaphthalene, polychlorinated biphenyls and photoinitiators in cigarette paper, which reduces the matrix effect and improves the sensitivity of the method, and has the advantages of simple operation, rapidity, accuracy, and good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0015] Figure 1 is a scanning electron microscope image of a spherical mesoporous carbon material provided in an embodiment of the present application;

[0016] Figure 2 is N of the spherical mesoporous carbon material provided in the embodiments of the present application 2 Adsorption-desorption curve diagram;

[0017] Figure 3 is a pore volume-pore size distribution diagram of the spherical mesoporous carbon material provided in the embodiments of the present application;

[0018] Figure 4 It is a schematic flow chart of a method for simultaneously detecting diisopropylnaphthalene, polychlorinated biphenyls and photoinitiators in cigarette paper provided in an embodiment of the present application;

[0019] Figure 5 It is a comparative schematic diagram of the response of the spherical mesoporous carbon material provided in the examples of the present application to DiPN, PCBs, and PIs compounds;

[0020] Figure 6 It is a schematic diagram comparing the response of the spherical mesoporous carbon material dosage to DiPN, PCBs, and PIs compounds provided in the examples of the present application;

[0021] Figure 7It is a comparative schematic diagram of the response of the vortex oscillation time to DiPN, PCBs, and PIs compounds provided in the examples of the present application;

[0022] Figure 8 It is a comparative schematic diagram of the response of the oscillation rate to DiPN, PCBs, and PIs compounds provided in the examples of the present application;

[0023] Fig. 9 This is a comparison chart of the effects of different adsorbents on reducing the matrix effect provided in the examples of the present application. DETAILED DESCRIPTION

[0024] The technical scheme of the preferred embodiment of the present application will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection claimed in this application.

[0025] An embodiment of the present application provides a method for preparing a spherical mesoporous carbon material, the method comprising: obtaining a sucrose solution; adding sodium polyacrylate to the sucrose solution; adding silica sol to the sucrose solution with sodium polyacrylate added, and mixing evenly; adding concentrated sulfuric acid to the sucrose solution with sodium polyacrylate and silica sol added, mixing evenly, and heating to react; washing the reaction product to neutrality, and then drying the reaction product; grinding the dried reaction product, and then calcining it in a nitrogen atmosphere; eliminating the silicon template in the reaction product to obtain a spherical mesoporous carbon material.

[0026] In some embodiments, the mass ratio of sucrose to sodium polyacrylate in the sucrose solution is 1:(0.0013-0.0022).

[0027] In some embodiments, the mass ratio of sucrose to sodium polyacrylate in the sucrose solution is 1:(0.0017-0.0018), preferably, 1:0.00175.

[0028] In some embodiments, the relationship between the mass of sucrose in the sucrose solution and the volume of the silica sol is 1 g: (0.56-0.66) mL; the relationship between the mass of sucrose in the sucrose solution and the volume of concentrated sulfuric acid is 1 g: (0.24-0.34) mL; the concentration of sucrose in the sucrose solution is (0.21-0.24) g / mL. Preferably, the relationship between the mass of sucrose in the sucrose solution and the volume of the silica sol is 1 g: 0.61 mL; the relationship between the mass of sucrose in the sucrose solution and the volume of concentrated sulfuric acid is 1 g: 0.29 mL; the concentration of sucrose in the sucrose solution is 0.228 g / mL.

[0029] In some embodiments, after adding silica sol to a sucrose solution to which sodium polyacrylate is added, stirring is performed at room temperature for 55 to 65 minutes to mix evenly; after adding concentrated sulfuric acid to a sucrose solution to which sodium polyacrylate and silica sol are added, stirring is performed for 55 to 65 minutes to mix evenly, and the stirred solution is placed in an oven at 95°C to 105°C for aging for 23 to 25 hours to increase the temperature for reaction; after washing the reaction product to neutrality, drying it in an oven at 75°C to 85°C to dry the reaction product; grinding the dried reaction product, calcining it at 850°C to 950°C in a nitrogen atmosphere for 2.5 to 3.5 hours; using a NaOH solution or a HF solution to eliminate the silicon template in the reaction product. Preferably, after adding silica sol to the sucrose solution to which sodium polyacrylate is added, stirring is performed for 60 minutes at room temperature to mix evenly; after adding concentrated sulfuric acid to the sucrose solution to which sodium polyacrylate and silica sol are added, stirring is performed for 60 minutes to mix evenly, and the stirred solution is placed in a 100°C oven for aging for 24 hours to increase the temperature for reaction; after washing the reaction product to neutrality, drying it in an 80°C oven to dry the reaction product; after grinding the dried reaction product, calcining it at 900°C in a nitrogen atmosphere for 3 hours; and using a NaOH solution or a HF solution to eliminate the silicon template in the reaction product.

[0030] Specifically, a one-pot method can be used to synthesize spherical mesoporous carbon materials, using sucrose as a carbon precursor, concentrated sulfuric acid as a catalyst, and LUDOX HS-40 silica sol as a template to obtain spherical mesoporous carbon materials (SMC). The amount of dispersant sodium polyacrylate (PAAS) was adjusted to prepare highly dispersed spherical mesoporous carbon materials SMC-PAAS15, SMC-PAAS20, and SMC-PAAS25.

[0031] Example 1

[0032] A method for preparing a highly dispersible spherical mesoporous carbon material is as follows:

[0033] (1) Accurately weigh 11.4 g of sucrose and place it in a 200 mL beaker containing 50 mL of deionized water. Add 15 mg of sodium polyacrylate (PAAS) as a dispersant and stir until fully dissolved.

[0034] (2) Quickly add 7 mL of LUDOX HS-40 silica sol and stir at room temperature for 60 min;

[0035] (3) Slowly add 3.25 mL of concentrated sulfuric acid to the solution and stir for 60 min;

[0036] (4) The stirred solution was placed in an oven at 100°C for aging for 24 hours. The obtained product was washed with distilled water until neutral and placed in an oven at 80°C for drying overnight.

[0037] (5) The dried product was ground and placed in an ark, and calcined at 900°C for 3 h in a nitrogen atmosphere. The silicon template was removed with a 2M NaOH solution, and the final sample (SMC-PAAS15) was obtained after drying.

[0038] Example 2

[0039] A method for preparing a highly dispersible spherical mesoporous carbon material is as follows:

[0040] (1) Accurately weigh 11.4 g of sucrose and place it in a 200 mL beaker containing 50 mL of deionized water. Add 20 mg of sodium polyacrylate (PAAS) as a dispersant and stir until fully dissolved.

[0041] (2) Quickly add 7 mL of LUDOX HS-40 silica sol and stir at room temperature for 60 min;

[0042] (3) Slowly add 3.25 mL of concentrated sulfuric acid to the solution and stir for 60 min;

[0043] (4) The stirred solution was placed in an oven at 100°C for aging for 24 hours. The obtained product was washed with distilled water until neutral and placed in an oven at 80°C for drying overnight.

[0044] (5) The dried product was ground and placed in an ark, and calcined at 900°C for 3 h in a nitrogen atmosphere. The silicon template was removed with a 2M NaOH solution, and the final sample (SMC-PAAS20) was obtained after drying.

[0045] Example 3

[0046] A method for preparing a highly dispersible spherical mesoporous carbon material is as follows:

[0047] (1) Accurately weigh 11.4 g of sucrose and place it in a 200 mL beaker containing 50 mL of deionized water. Add 25 mg of sodium polyacrylate (PAAS) as a dispersant and stir until fully dissolved.

[0048] (2) Quickly add 7 mL of LUDOX HS-40 silica sol and stir at room temperature for 60 min;

[0049] (3) Slowly add 3.25 mL of concentrated sulfuric acid to the solution and stir for 60 min;

[0050] (4) The stirred solution was placed in an oven at 100°C for aging for 24 hours. The obtained product was washed with distilled water until neutral and placed in an oven at 80°C for drying overnight.

[0051] (5) The dried product was ground and placed in an ark, and calcined at 900°C for 3 h in a nitrogen atmosphere. The silicon template was removed with a 2M NaOH solution, and the final sample (SMC-PAAS25) was obtained after drying.

[0052] Comparative Example 1

[0053] A method for preparing a spherical mesoporous carbon material (SMC) is as follows:

[0054] (1) Accurately weigh 11.4 g of sucrose, place it in a 200 mL beaker containing 50 mL of deionized water, and stir until fully dissolved;

[0055] (2) Quickly add 7 mL of LUDOX HS-40 silica sol and stir at room temperature for 60 min;

[0056] (3) Slowly add 3.25 mL of concentrated sulfuric acid to the solution and stir for 60 min;

[0057] (4) The stirred solution was placed in an oven at 100°C for aging for 24 hours. The obtained product was washed with distilled water until neutral and placed in an oven at 80°C for drying overnight.

[0058] (5) The dried product was ground and placed in an ark, calcined at 900 °C for 3 h in a nitrogen atmosphere, and the silicon template was removed with a 2 M NaOH solution. The final sample was obtained after drying.

[0059] Characterization of spherical mesoporous carbon materials:

[0060] The surface morphology of the prepared spherical mesoporous carbon material was analyzed using a scanning electron microscope (SEM). Figure 1 The scanning electron microscope images of the mesoporous carbon materials synthesized without dispersant and with different amounts of dispersant PAAS of 15 mg, 20 mg, and 25 mg are shown. Specifically, Figure 1 In the figure, the images of the mesoporous carbon material (SMC) synthesized without adding dispersant are A and B, the images of the mesoporous carbon material (SMC-PAAS15) synthesized by adding 15 mg of dispersant PAAS are C and D, the images of the mesoporous carbon material (SMC-PAAS20) synthesized by adding 20 mg of dispersant PAAS are E and F, and the images of the mesoporous carbon material (SMC-PAAS25) synthesized by adding 25 mg of dispersant PAAS are G and H. The results are shown in Figure 1 As shown in the figure, the prepared mesoporous carbon material has a spherical morphology and a rough surface. Due to the different amounts of dispersant, the process of carbon source coating the template is affected, and the specific surface area of ​​the material is different. The synthesized spherical mesoporous carbon material has a uniform particle size, good material dispersion, and no large amount of aggregation. When the amount of dispersant is 25 mg, some agglomeration occurs, resulting in a decrease in the specific surface area of ​​the material. Figure 2 and Figure 3 N of SMC, SMC-PAAS15, SMC-PAAS20 and SMC-PAAS25 respectively 2 Adsorption-desorption curve and pore size distribution diagram. Figure 2 and Figure 3 As shown in Table 1, the synthesized mesoporous carbon material presents a type IV isotherm trend, and the pore size distribution diagram shows that the material has peaks at about 3nm and 5nm. Combined with the results in Table 1, SMC-PAAS20 has the largest specific surface area, reaching 771m 2 / g, the pore diameter and pore volume reached 3.2nm and 0.37cm 3 / g, proving the successful synthesis of spherical mesoporous carbon materials with mesoporous structure and adjustable pore size.

[0061] Table 1

[0062]

[0063] In Table 1, S BET :According to the nitrogen adsorption isotherm at p / p by BET method 0 =Specific surface area calculated in the range of 0.05-0.2; D p : The average pore size was obtained from the adsorption branch of the nitrogen adsorption isotherm by the BJH method; V total :According to p / p 0 = 0.99 for the total pore volume.

[0064] Cigarette paper is the most common type of tobacco material, which wraps tobacco and cigarettes. With the rapid development of the industry, strict requirements are put forward on the safety of cigarette paper, and more stringent limit standards are formulated, such as diisopropylnaphthalene, polychlorinated biphenyls, and photoinitiators.

[0065] Diisopropylnaphthalene (DiPN) is colorless, odorless, and has strong dye solubility. It is widely used in paper and other fields. It may cause reproductive system abnormalities through direct and indirect contact. Diisopropylnaphthalene in paper, including food contact paper, usually comes from recycled paper. Polychlorinated biphenyls (PCBs) are a class of persistent organic pollutants and are the first controlled substances listed in the Stockholm Convention on Persistent Organic Pollutants. PCBs are easily soluble in fats and organic solvents, and are extremely difficult to decompose. They are easily enriched in organisms and can migrate over long distances in the environment. They are also substances of great concern in the fields of soil, surface water, food, and food contact paper. Photoinitiators (PIs) are important components of UV-curable inks. They are mainly distributed in packaging printing inks and migrate through contact. Low molecular weight photoinitiators and monomers in inks can irritate the skin, thus posing potential hazards to human health.

[0066] Cigarette paper contains complex chemical components, with relatively low content, mostly in trace or ultra-trace amounts. There is a lot of matrix interference in sample analysis, which places high demands on detection methods and detection instruments. Commonly used detection methods use different sample pretreatment and instrument analysis conditions to determine the content of each compound in cigarette paper, which has the disadvantages of cumbersome steps, time-consuming, long detection cycle, and slow detection speed.

[0067] In order to quickly and accurately detect the content of diisopropylnaphthalene, polychlorinated biphenyls, and photoinitiators in cigarette paper, the present invention uses the prepared highly dispersed spherical mesoporous carbon material as a dispersed solid phase extraction adsorbent, combined with a gas chromatography-mass spectrometer, to establish a detection method for simultaneously analyzing diisopropylnaphthalene, polychlorinated biphenyls, and photoinitiators in cigarette paper. Specifically, combined with Figure 4 The method comprises: cutting cigarette paper into pieces; putting the cut cigarette paper into a dichloromethane extraction solvent, then adding three mixed internal standard solutions of deuterated pyrene, deuterated phenanthrene and deuterated acenaphthene, and ultrasonic extraction; extracting the extract, adding the spherical mesoporous carbon material prepared by the preparation method of the spherical mesoporous carbon material provided by any embodiment of the present application to the extract, vortexing, and centrifuging after oscillation; taking the supernatant after centrifugation and entering the gas chromatography-mass spectrometer for analysis to detect diisopropylnaphthalene, polychlorinated biphenyls and photoinitiators in the cigarette paper. The cigarette paper can be selected from cigarette tipping paper, lining paper and box packaging paper.

[0068] In some embodiments, the mass ratio of the cigarette paper to the mass ratio of the spherical mesoporous carbon material is 1:(0.035-0.045); the vortex oscillation time is 25min-35min, and the oscillation rate is 550rpm-650rpm. Preferably, the mass ratio of the cigarette paper to the mass ratio of the spherical mesoporous carbon material is 1:0.04; the vortex oscillation time is 30min, and the oscillation rate is 600rpm.

[0069] In some embodiments, the chromatographic conditions are: helium as carrier gas, the injection port temperature is 300°C, the injection volume is 1 μL, and the injection mode is splitless injection; the column oven temperature program is: 60°C, hold for 2 minutes, increase the temperature to 170°C at a rate of 40°C / min, then increase the temperature to 180°C at a rate of 2°C / min, hold for 10 minutes, and finally increase the temperature to 300°C at a rate of 25°C / min, and hold for 20 minutes.

[0070] In some embodiments, the mass spectrometry conditions are: the transfer line temperature is 300° C., the ion source temperature is 280° C., the quadrupole temperature is 150° C., the solvent delay is 6 min, and the selected ion mode is used.

[0071] The present application uses the synthesized SMC-PAAS20 highly dispersed spherical mesoporous carbon material as a dispersed solid phase extraction adsorbent, combined with a gas chromatography-mass spectrometer, to establish a detection method for simultaneously analyzing diisopropylnaphthalene, polychlorinated biphenyls, and photoinitiators in cigarette paper.

[0072] Example 4

[0073] Preparation of mixed internal standard solution:

[0074] Mixed internal standard solution 1: Accurately pipette 1 mL of 1000 mg / L deuterated pyrene, 1000 mg / L deuterated phenanthrene, and 1000 mg / L deuterated acenaphthene standard solutions into 10 mL brown volumetric flasks, and dilute to volume with dichloromethane to prepare 100 mg / L mixed internal standard solutions 1 of deuterated pyrene, deuterated phenanthrene, and deuterated acenaphthene.

[0075] Mixed internal standard solution 2: Take 1 mL of mixed internal standard solution 1, place it in a 10 mL brown volumetric flask, and dilute to volume with dichloromethane to obtain a 10 mg / L mixed internal standard solution 2 of deuterated pyrene, deuterated phenanthrene, and deuterated acenaphthene.

[0076] Preparation of diisopropylnaphthalene standard solution:

[0077] Diisopropylnaphthalene standard solution 1: Accurately weigh 0.01 g of diisopropylnaphthalene isomer mixture standard, transfer it to a 100 mL brown volumetric flask, and dilute to volume with dichloromethane to prepare a 100 mg / L diisopropylnaphthalene standard solution 1.

[0078] Diisopropylnaphthalene standard solution 2: Transfer 1 mL of diisopropylnaphthalene standard solution 1 to a 10 mL volumetric flask and dilute to volume with dichloromethane to obtain a 10 mg / L diisopropylnaphthalene standard solution 2.

[0079] Preparation of PCB standard solution:

[0080] PCB standard solution 1: The purchased mixed standard solution of 7 kinds of PCBs is 100 mg / L and is used as PCB standard solution 1.

[0081] Polychlorinated biphenyl standard solution 2: Transfer 1 mL of polychlorinated biphenyl standard solution 1 to a 10 mL volumetric flask and dilute to volume with dichloromethane to obtain a 10 mg / L polychlorinated biphenyl standard solution 2.

[0082] Preparation of photoinitiator standard solution:

[0083] Photoinitiator standard solution 1: The purchased mixed standard solution of 18 photoinitiators is 1000 mg / L. Transfer 1 mL of the standard solution to a 10 mL brown volumetric flask, dilute to volume with dichloromethane to prepare a 100 mg / L photoinitiator standard solution 1.

[0084] Photoinitiator standard solution 2: Transfer 1 mL of photoinitiator standard solution 1 to a 10 mL brown volumetric flask and dilute to volume with dichloromethane to obtain a 10 mg / L photoinitiator standard solution 2.

[0085] Preparation of diisopropylnaphthalene and polychlorinated biphenyls series standard working solution: select six clean brown volumetric flasks, add 0.05mL, 0.1mL, 0.5mL of diisopropylnaphthalene standard solution 2 and polychlorinated biphenyls standard solution 2 to three different 10mL volumetric flasks respectively, add 0.2mL mixed internal standard standard solution 2, be diluted to 10mL with dichloromethane to obtain diisopropylnaphthalene and polychlorinated biphenyls content is 0.5μg, 1μg, 5μg series standard working solution; Add 0.1mL, 0.2mL, 0.5mL of diisopropylnaphthalene standard solution 1 and polychlorinated biphenyls standard solution 1 to three different 10mL volumetric flasks respectively, add 0.2mL mixed internal standard standard solution 2, be diluted to 10mL with dichloromethane to obtain diisopropylnaphthalene and polychlorinated biphenyls content is 10μg, 20μg, 50μg series standard working solution.

[0086] Preparation of photoinitiator series standard working solutions: select six clean brown volumetric flasks, add 0.05mL, 0.1mL, and 0.5mL of photoinitiator standard solution 2 respectively, add 0.2mL of mixed internal standard standard solution 2, and dilute to 10mL with dichloromethane to obtain 0.5μg, 1μg, and 5μg of photoinitiator series standard working solutions; add 0.1mL, 0.2mL, and 0.5mL of photoinitiator standard solution 1 respectively to obtain photoinitiator series standard working solutions with contents of 10μg, 20μg, and 50μg.

[0087] The diisopropylnaphthalene compound is selected from 1,3-diisopropylnaphthalene, 1,7-diisopropylnaphthalene, 2,6-diisopropylnaphthalene, 2,7-diisopropylnaphthalene, 1,6-diisopropylnaphthalene, 1,4-diisopropylnaphthalene and 1,5-diisopropylnaphthalene.

[0088] The polychlorinated biphenyl compound is selected from 2,2',5-trichlorobiphenyl, 2,4,4'-trichlorobiphenyl, 2,2',5,5'-tetrachlorobiphenyl, 2,2',4,5,5'-pentachlorobiphenyl, 2,2',3,4,4',5-hexachlorobiphenyl, 2,2',4,4',5,5'-hexachlorobiphenyl and 2,2',3,4,4',5,5'-heptachlorobiphenyl.

[0089] The photoinitiator is selected from 2-hydroxy-2-methyl-1-phenylpropanone, methyl benzoylformate, benzophenone, 2-methylbenzophenone, 1-hydroxycyclohexylphenyl ketone, ethyl p-N,N-dimethylaminobenzoate, 3-methylbenzophenone, 4-methylbenzophenone, 2,2-dimethoxy-2-phenylacetophenone, methyl o-benzoylbenzoate, isooctyl p-dimethylaminobenzoate, 2-methyl-1-(4-methylthio)phenyl-2-morpholinyl-1-propanone, 4-isopropylthioxanthone, 2-isopropylthioxanthone, biphenylbenzophenone, 2,4-diethylthioxanthone, 4,4-bis(dimethylamino)benzophenone and 4,4-bis(diethylamino)benzophenone.

[0090] The internal standards used were deuterated pyrene, deuterated phenanthrene, and deuterated acenaphthene.

[0091] Extraction of blank cigarette paper sample: Weigh 1g blank cigarette paper sample and place it in a stoppered conical flask. Add 20mL of dichloromethane, extract by ultrasonic for 40min and let stand. After filtering the extract to remove paper debris, place it in a 50mL brown glass bottle and store it in a refrigerator.

[0092] Optimize sample pretreatment conditions: add 10 μg of diisopropylnaphthalene, polychlorinated biphenyls, and standard solutions of photoinitiators to the blank cigarette paper sample extract. Optimize a series of important factors that affect the performance of dispersed solid phase extraction, including different specifications of spherical mesoporous carbon materials (SMC, SMC-PAAS15, SMC-PAAS20, SMC-PAAS25), the amount of spherical mesoporous carbon material adsorbent used (20 mg, 30 mg, 40 mg, 50 mg), vortex oscillation time (20 min, 30 min, 40 min) and oscillation rate (400 rpm, 600 rpm, 800 rpm). Figure 5-Figure 8 As shown in the figure, the optimal conditions were selected according to the spike recovery rate: different specifications of spherical mesoporous carbon materials: SMC-PAAS20; adsorbent dosage: 40 mg; vortex oscillation time: 30 min; oscillation rate: 600 rpm. Subsequently, the method was established and verified under the optimal conditions.

[0093] Method validation: Under the optimal conditions, the linear range, detection limit, spike recovery rate, etc. of the method were investigated. As shown in Table 2, the method has a good linear relationship (R 2 =0.9934-0.9998), the detection limit was calculated by 3 times the signal-to-noise ratio, and the detection limit was 0.9-5.9 ng / mL. The recovery rate was tested at three spiking levels of 2μg, 5μg and 10μg, and the spiked recovery rate of this method was 84.1%-106.7%, with a relative standard deviation (RSD, 1.9%-9.8%), indicating that this method has high accuracy and sensitivity and good repeatability.

[0094] Table 2

[0095]

[0096]

[0097] In Table 2, 2,7-diisopropylnaphthalene, 1,6-diisopropylnaphthalene, 1,4-diisopropylnaphthalene and 1,5-diisopropylnaphthalene are four consecutive peaks, and the sum of the peak areas of the four compounds is substituted into the linear regression equation for quantitative analysis.

[0098] Actual sample testing: Five cigarette papers (including cigarette tipping paper, lining paper and box packaging paper) were randomly selected, and the samples were cut into 0.5cm*0.5cm pieces and mixed evenly. Weigh 1g and place it in a stoppered conical flask, add 20mL of dichloromethane extraction solvent, add 40μL of three mixed internal standard solutions of deuterated pyrene, deuterated phenanthrene and deuterated acenaphthene, ultrasonic extraction for 40min, extract 4mL of extract, add 40mg of the prepared highly dispersed spherical mesoporous carbon material SMC-PAAS20 as a dispersed solid phase extraction adsorbent, oscillate for 30min at a speed of 600rpm, centrifuge for 5min after oscillation, and take the supernatant for gas chromatography-mass spectrometry analysis.

[0099] The ratio of the quantitative ion peak area of ​​the compound in the series of standard solutions to the quantitative ion peak area of ​​the internal standard is the ordinate, and the ratio of the concentration of each compound in the series of standard solutions to the internal standard concentration is the abscissa. The linear regression equation of the series of standard solutions is drawn, and the internal standard method is used to quantify the content of the target compound in the sample. Results Sample 3 only contains isooctyl p-dimethylaminobenzoate, and its content is 3.5 mg / mL. 2 .

[0100] Comparative Example 2

[0101] Cigarette paper samples were extracted with dichloromethane, and the extract was directly analyzed by gas chromatography-mass spectrometry, which would cause contamination to the chromatographic column, mass spectrometer inlet and ion source, affecting the detection sensitivity and accuracy. Commonly used adsorbents include N-propylethylenediamine adsorbent (PSA), C18, etc. The experiment investigated the purification effect of different adsorbents on non-target compounds in the matrix. Dispersive solid phase extraction kit 1, which consists of 150 mg anhydrous magnesium sulfate and 50 mg N-propylethylenediamine (PSA), is a 2 mL kit referred to as PSA adsorbent, and dispersed solid phase extraction kit 2, which consists of 150 mg anhydrous magnesium sulfate, 50 mg PSA and C18, is a 2 mL kit referred to as PSA+C18 adsorbent.

[0102] Under the optimal conditions studied, comparative experiments with different adsorbents were carried out.

[0103] Chromatographic conditions: HP-5MS chromatographic column (30m×0.25mm×0.25μm); helium as carrier gas; injection port temperature of 300℃; injection volume of 1μL; injection mode of splitless injection. The column oven temperature program is: 60℃, hold for 2min, increase to 170℃ at a rate of 40℃ / min, then increase to 180℃ at a rate of 2℃ / min, hold for 10min, and finally increase to 300℃ at a rate of 25℃ / min, hold for 20min.

[0104] Mass spectrometry conditions: transfer line temperature of 300°C, ion source temperature of 280°C, quadrupole temperature of 150°C, solvent delay of 6 min, full scan mode.

[0105] The specific steps are as follows:

[0106] (1) Weigh 1 g of cigarette paper sample and place it in a stoppered conical flask. Add 20 mL of dichloromethane and perform ultrasonic extraction for 40 min. The extract is divided into four groups and placed in 12 mL brown sample bottles respectively.

[0107] (2) Take 1 mL of the extract obtained in step (1) and filter it through a 0.22 μm organic filter membrane.

[0108] (3) In the second group, 4 mL of the extract obtained in step (1) was added with 40 mg of SMC-PAAS20 spherical mesoporous carbon material, and the mixture was vortexed at 600 rpm for 30 min and centrifuged. The supernatant was then sampled.

[0109] (4) The third group added the extract obtained in step (1) into the PSA kit, vortexed and centrifuged, and extracted the supernatant for sampling.

[0110] (5) The extract obtained in the fourth group of step (1) was added to the PSA+C18 kit, shaken and centrifuged, and the supernatant was extracted for sampling.

[0111] from Fig. 9 It can be clearly seen that the spherical mesoporous carbon material SMC-PAAS20 has the best impurity removal effect compared with other adsorbents when the retention time is between 5-15min and 25-30min, reducing the matrix effect and thus improving the detection sensitivity and accuracy.

[0112] A highly dispersed spherical mesoporous carbon material was successfully synthesized by the method provided in the embodiments of the present application. The highly dispersed spherical mesoporous carbon material has a developed pore structure and a high specific surface area, which can provide more adsorption sites. The mesoporous structure is conducive to the rapid diffusion of the material in the solution, which can improve the adsorption performance of the material and enhance the adsorption amount of the material on non-target substances. Using the highly dispersed spherical mesoporous carbon ball material SMC-PAAS20 as a dispersed solid phase extraction adsorbent, a detection method for simultaneously analyzing diisopropylnaphthalene, polychlorinated biphenyls, and photoinitiators in cigarette paper was developed. The present invention is the first to use a highly dispersed spherical mesoporous carbon material as an adsorbent combined with dispersed solid phase extraction technology to detect diisopropylnaphthalene, polychlorinated biphenyls, and photoinitiators in cigarette paper. The prepared highly dispersed spherical mesoporous carbon material has excellent performance as a dispersed solid phase extraction adsorbent, and shows good results for the simultaneous analysis of multiple targets.

[0113] Based on the above-mentioned embodiments of the present application, in the absence of explicit negation or conflict, the technical features of one embodiment may be beneficially combined with one or more other embodiments.

[0114] Although some specific embodiments of the present application have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are only for illustration and not for limiting the scope of the present application. It should be understood by those skilled in the art that the above embodiments may be modified or some technical features may be replaced by equivalents without departing from the scope and spirit of the present application. The scope of the present application is defined by the appended claims.

Claims

1. A method for preparing a spherical mesoporous carbon material, characterized in that: include: Obtain sucrose solution; Adding sodium polyacrylate to the sucrose solution; Add silica sol to the sucrose solution with sodium polyacrylate, and mix well; Add concentrated sulfuric acid to the sucrose solution containing sodium polyacrylate and silica sol, mix well, and heat to react; washing the reaction product to neutrality, and then drying the reaction product; The dried reaction product was ground and then calcined in a nitrogen atmosphere; The silicon template in the reaction product is eliminated to obtain spherical mesoporous carbon materials.

2. The method according to claim 1, characterized in that The mass ratio of sucrose to sodium polyacrylate in the sucrose solution is 1:(0.0013~0.0022).

3. The method according to claim 1, characterized in that The mass ratio of sucrose to sodium polyacrylate in the sucrose solution is 1:(0.0017~0.0018).

4. The method according to claim 1, characterized in that: The relationship between the mass of sucrose in the sucrose solution and the volume of silica sol is 1g: (0.56-0.66)mL; The relationship between the mass of sucrose in a sucrose solution and the volume of concentrated sulfuric acid is 1 g: (0.24-0.34) mL; The concentration of sucrose in the sucrose solution is (0.21~0.24) g / mL.

5. The method according to claim 1, characterized in that After adding silica sol to the sucrose solution with sodium polyacrylate, stir at room temperature for 55 to 65 minutes to mix evenly; After adding concentrated sulfuric acid to the sucrose solution containing sodium polyacrylate and silica sol, stir for 55 to 65 minutes to mix evenly, and place the stirred solution in an oven at 95 to 105 degrees Celsius for aging for 23 to 25 hours to increase the temperature for reaction; After washing the reaction product to neutrality, place it in an oven at 75°C to 85°C to dry the reaction product; The dried reaction product was ground and then calcined at 850°C to 950°C for 2.5h to 3.5h in a nitrogen atmosphere; The silicon template in the reaction product is eliminated using a NaOH solution or a HF solution.

6. A spherical mesoporous carbon material, characterized in that: The specific surface area of ​​spherical mesoporous carbon materials is 705-771 m 2 / g.

7. The spherical mesoporous carbon material according to claim 6, characterized in that: The pore volume of spherical mesoporous carbon materials is 0.36-0.37 cm 3 / g.

8. A method for simultaneously detecting diisopropylnaphthalene, polychlorinated biphenyls and photoinitiators in cigarette paper, characterized in that: include: Cut the cigarette into pieces with paper; Put the shredded cigarette paper into dichloromethane extraction solvent, then add three mixed internal standard solutions of deuterated pyrene, deuterated phenanthrene and deuterated acenaphthene, and perform ultrasonic extraction; Extracting the extract, adding the spherical mesoporous carbon material prepared by the method for preparing the spherical mesoporous carbon material according to any one of claims 1 to 5 to the extract, vortexing, shaking and centrifuging; The supernatant after centrifugation was taken and analyzed by gas chromatography-mass spectrometry to detect diisopropylnaphthalene, polychlorinated biphenyls and photoinitiators in cigarette paper.

9. The method according to claim 7, characterized in that: The mass ratio of cigarette paper to spherical mesoporous carbon material is 1:(0.035-0.045); The vortex oscillation time is 25 min to 35 min, and the oscillation rate is 550 rpm to 650 rpm.

10. The method according to claim 7, characterized in that The chromatographic conditions were as follows: helium as carrier gas, injection port temperature of 300 °C, injection volume of 1 μL, and injection mode of splitless injection; The column oven temperature program was as follows: 60°C, hold for 2 min, increase to 170°C at a rate of 40°C / min, then increase to 180°C at a rate of 2°C / min, hold for 10 min, and finally increase to 300°C at a rate of 25°C / min, hold for 20 min; The mass spectrometry conditions were as follows: the transfer line temperature was 300°C, the ion source temperature was 280°C, the quadrupole temperature was 150°C, the solvent delay was 6 min, and the selected ion mode was used.

Citation Information

Cited By

  • Preparation method and application of zinc gluconate graded porous carbon adsorbent

    CN121372345A